A Review of the Impact of Spontaneous Combustion on Slope Stability in Coal Mine Waste Dumps - Phu Minh Vuong Nguyen (Applied Sciences, 2025)
Mining waste from both underground and open-pit mines is typically placed in surface sites known as mine waste dumps. Over time, as large volumes of mining waste accumulate, these dumps become higher due to the limited surface area allocated to dumping. Ensuring the stability of mine waste dumps is a major concern for both mining operations and local governments due to safety risks to the dumps themselves and their surrounding environments. In some cases of mine waste dump, spontaneous combustion poses a significant challenge, affecting not only the environment but also the slope stability of mine waste dumps. This review synthesizes existing research on the mechanisms of spontaneous combustion, its thermal effects, and the implications for geomechanical stability in mine waste dumps. It also examines methods for monitoring and controlling these processes, identifies gaps in the current research, and suggests directions for future studies. The review also reveals that combustion-induced temperature changes, material degradation, and gas generation significantly impact the geotechnical properties of building material dumps, contributing to slope failure. This review is expected to provide valuable insights that help mining authorities assess risks, minimize impacts, and implement preventive measures to mitigate unexpected spontaneous combustion-induced slope failures in mine waste dumps.